IMPROVEMENT OF ADAPTATION TO STRUCTURES REMOVABLE DENTURES IN PATIENTS WITH ISCHEMIC HEART DISEASE - N.A. Ryabushko; V.N. Dvornik; I.V. Pavlish; G.N. Balya (Український стоматологічний альманах)
The aim is to improve the process of adaptation to removable designs of dentures in patients with coronary heart disease.